Fall armyworm A new invasive pest of maize in India - Narayanamma, V Lakshmi; Reddy, M Lavakumar; Krishnaiah, N V (Indian Farming, 2020)
Fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is native to the America, spread to the African continent in January 2016. It was first noticed in India on May 18th, 2018 in Shimoga district of Karnataka. Currently, over 40 countries mostly of Africa and North and South America have identified the pest within their borders.